Statistical fact of students' background and academic achievement in higher educational institution - Hasan, Noshida; Adam, Mohd. Bakri; Mustapha, Norwati; Midi, Habshah (Elsevier, 2010)
The differences in academic achievement among students are a topic that has drawn interest of many academic researchers and Malaysian society. This paper describes the results of a detailed statistical analysis relating to the degree classification obtained at the end of their studies (first class, second class upper or second class lower) between undergraduate students and their backgrounds. In this study, students’ data from one of the higher educational institution in Malaysia from 1997 to 2006 are used. Visual analysis of categorical data techniques had been applied to reveal the students’ academic achievement pattern from various backgrounds.The findings can assist the institution in determining future policy on student admissions and to provide the necessary plans to improve student achievement.